KESUKAAN PANELIS TERHADAP KARTU MONITORING ORANG TUA UNTUK MENYIKAT GIGI SISWA SDN DESA PADANGSAMBIAN KOTA DENPASAR TAHUN 2020 - Ni Made Sirat; Ni Ketut Ratmini; Asep Arifin Senjaya (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2022)
In Indonesia, there was an increase in the prevalence of dental caries in the Indonesian population in 2007, from 43.4% to 53.2% in 2013 (Kemenkes RI., 2013). Riskesdas data (2018) records the proportion of dental and oral problems in Indonesia at 57.6%. Bali Province is one of the provinces in Indonesia that has a prevalence of dental caries experience which is higher than the national prevalence of 68.2% (Septarini and Pitriyanti, 2016). This study aims to determine the differences in panelists' preference for parental monitoring cards for brushing teeth at SDN Padangsambian Village Denpasar City 2020. The design of this quasi-experimental study was in the form of a hedonic test, with a post-test design only without control. The research was conducted at SDN 12, 2, 8 Padangsambian Village, Denpasar City, October-November 2020. The research population was all mothers and parents of students at SDN 12, SDN 2, and SDN 8 Padangsambian. Univariate data analysis: frequency, range, percentage. Differences in panelists' preference for color and monitoring card design were analyzed using the One-Sample Kolmogorov-Smirnov Test. The results of the study were 83.7% of panelists liked and really liked the blue card color. There were no panelists who did not really like the blue card. Test for differences in color preference of monitoring cards using the One-Sample Kolmogorov-Smirnov Test. The test results obtained sig value: 0.00. The test for differences in preference for monitoring card designs also uses the One-Sample Kolmogorov-Smirnov Test. The test results obtained sig value: 0.00. Conclusion: the blue color and the Model 2 monitoring card design are favored by hedonic test panelists. There is a significant difference in the panelists' preference for yellow, blue and green. There is a significant difference in the panelists' preference for card models 1, 2, and 3.